(untitled) (Research, Society and Development, 2021)
The bee wax has great historical importance and has been present since the evolution of civilizations. Currently, besides several uses of the wax, its recovery is indispensable for the rational management of swarms by beekeepers. The wax can be recovered from the combs using different techniques, however the conditions of the pre-extraction combs, such as their size, can influence the wax yield. Thus, studies must still be carried out to standardize the techniques and processes for extracting the wax from the combs, in order to improve the wax yield. This study aimed to evaluate the recovery of Apis mellifera wax according to the size of the comb using an alternative extraction technique. First, the influence of the comb size on wax recovery was evaluated. We used brown color combs, which were broken down into four sizes, each size representing a treatment, namely: Treatment I - 25 cm2; Treatment II - 16 cm2; Treatment III - 9 cm2 and Treatment IV - 4 cm2. Combs were submitted to the "internal strain" technique for 30 minutes of extraction, after boiling the water. The wax recovery was superior in treatment III (P <0.05). Wax recovery from treatment IV was similar to treatment II, which, in turn, showed similar recovery to treatment I (P <0.05). Besides, the wax recovery using 9 cm2 combs was evaluated by the commercial technique of "steam extraction" and the alternative technique of "internal strain", for a period of 30 minutes. The “internal strain” technique showed greater wax recovery than the “steam extraction” technique (P <0.01). The use of alternative wax recovery together with 9 cm2 combs size may optimize the wax extraction process, in terms that it decreases the time of exposure of the wax to heat, and thus positively affect the quality of the final product.